The effect of different concentration of gallic acid on sperm mobility and inhibition of microorganisms in liquid preserved boar semen - Lustykova, Alena; Frydrychova, Soňa; Seifert, Josef; Kucharova, Stanislava; Truneckova, Jana; Rozkot, Miroslav; Vydržalová, Markéta; Mosio, Petra; Brožková, Iveta; Moťková, Petra (My University, 2019)
The objective of this study was to investigate the effect of different concentration of gallic acid added to boar semen extender on inhibition of microorganisms and their influence on sperm motility. The selected concentrations added to boar semen extender had no effect on initial sperm motility (p<0.05) unlike higher concentrations of gallic acid. Nine ejaculates from 4 healthy and fertile AI boars were used for this study. Different concentration of gallic acid (GA1, 2, 3) was added to boar extender BTS without antibiotic (BTS0) in dilution rate of 1+2, 1+4 and 1+8 and stored at 17°C up to 48h for everyday evaluation. Sperm motility was affected by storage time, the dilution ratio and concentration of GA (p<0.05). Significant differences (p<0.05) from total mean values of sperm motility were found between samples BTS0 70.21% vs. BTS0+GA2 57.87% and BTS0+GA3 58.89%. Microorganisms were not significantly inhibited by any of tested concentration of GA1, 2 and 3 (p>0.05). In conclusion, utilization of tested concentration of gallic acid as a potential substitute for antibiotics in boar semen extender is not possible because their low activity in the reduction of microorganisms was found in the tested samples and also GA2 and GA3 concentrations decreased sperm motility during preservation. Therefore, it is necessary to research other potential substances for a possible replacement for antibiotics in boar semen extender.
Keywords: boar semen; gallic acid; microorganisms; sperm motility